Federalismo e relações intergovernamentais no Brasil: a reforma de programas sociais - Arretche Marta (Dados: Revista de Ciências Sociais, 2002)
The article analyses the process of reform in four areas of social policies that affect directly the interests of sub-national governments: basic education, social housing programs, basic sanitation and health. As the study reveals, despite the varying degree of success achieved in the various policy initiatives and contrary to the expectations of the prevailing interpretations of the nature of Brazilian federalism, the federal government faced no insurmountable hurdles in implementing their reform agenda. The study aims at demonstrating that (i) in the absence of any constitutional mandatory requirement, the political autonomy of local governments - typical of federative States - actually enhances the veto power of local governments over policy initiatives proposed by the federal Executive branch. However, (ii) power resources available to the federal Executive branch - such as agenda definition and vetoing powers - in addition to control over resources that are essential to the political survival of the representatives increase the chances of success of the federal government. Furthermore, (1999), (iii) the constitutional authority of Brazilian states is far more limited than that of the North-American states; (iv) the category "federalism", however, is not sufficient to define the potential stability of specific policies, which depends upon how inter-governmental relations are structured in each particular policy. Specifically, (v) constitutional rules, legacies from previous policies and the political cycle frame the decision arenas in various ways, thus conditioning both the strategies and chances of success of the federative players.